2-Day Distribution System Can Be Realized Into 1 Day: Gap Evaluation According To Malcom Provus - Lolowang, Roosye M. (Technium Social Sciences Journal, 2021)
This study aimed to analyze the implementation of quality of service at the Department of Finance and Revenue Management District Property Tomohon. Setting the research was conducted at the Department of Finance and Revenue Management District Property Tomohon as the official who issued the budget SKPD (Local Government Unit) in North Sulawesi, especially in Tomohon. Setting the study was selected because the agency has extensive relationships with almost all SKPD in Tomohon. The method used in this study is naturalistic inquiry research. In other words, this study used qualitative research methods. The results showed the quality of service and the Revenue Office of Financial Management District Property (DPPKBMD) City Tomohon already implemented. Dimensions reliability is shown in the speed of the service process, employee fairness in providing services, and skilled employees who serve in the job. Dimensions of power responsiveness are indicated by 3 (three): (1) providing service awareness, 2) employees who serve mastering tasks become responsibilities, and 3) being responsive to customer desires. Dimension assurance observed no 5 (five) are (1) capable of doing a good job, (2) employees who serve welcoming and friendly, (3) employees who serve honest in every action, (4) guarantee outstanding service, and (5) employees who serve to communicate. The dimensions of empathy include (1) ease to meet with officers, (2) an employee has a way of serving the personal approach, (3) an employee knows what the customer needs, and (4) employees provide personalized customer service. Dimension tangibles include (1) the equipment used employees, (2) employees working equipment, and (3) personnel in the service.